Analysis of Language Anxiety: A Study in English Speaking Classes among Vocational Students - Romadhon, Syaefani Arif; Indrayanti, Iin; Qurohman, M Taufik (Universitas Dian Nuswantoro, 2023)
Abstract. This study is intended to determine the factors that cause student anxiety in speaking in English, and solutions to overcome this anxiety. This research was carried out at the vocational campus Harapan Bersama Polytechnic in 11 study programs with 177 participants. This research used qualitative method. The data were collected using questionnaires and interviews. The results of the questionnaire analysis show that the highest cause of anxiety is non-teacher feedbacks and the solution to overcome the anxiety problem is individual preferences. In addition, based on the interview analysis, the cause of anxiety was the influence of regional dialect spoken in northern Java coastal areas (Tegal, Brebes, Slawi, Pemalang, Bumiayu, Cirebon). Lecturers and educational institutions must consider the curriculum and students’ psychological condition, so it is hoped that it can reduce students’ anxiety level.Keywords: problem solution; psychological condition; speaking anxiety Abstrak. Penelitian ini dimaksudkan untuk mengetahui faktor-faktor yang menyebabkan kecemasan mahasiswa dalam berbicara dalam bahasa Inggris, dan solusi untuk mengatasi kecemasan tersebut. Penelitian ini dilaksanakan di kampus vokasi Politeknik Harapan Bersama di 11 program studi dengan 177 subjek. Penelitian ini menggunakan metode kualitatif. Data dikumpulkan menggunakan kuesioner dan wawancara. Hasil analisis kuesioner menunjukkan bahwa penyebab kecemasan tertinggi adalah tidak adanya koreksi dari dosen, dan solusi untuk mengatasi masalah kecemasan tersebut adalah preferensi individu. Selain itu, berdasarkan analisis wawancara, penyebab kegelisahan adalah pengaruh dialek daerah, yaitu dialek pesisir Jawa bagian utara (Tegal, Brebes, Slawi, Pemalang, Bumiayu, Cirebon). Dosen dan institusi pendidikan harus mempertimbangkan kurikulum dan kondisi psikologis mahasiswa, sehingga diharapkan dapat mengurangi tingkat kecemasan mahasiswa.Kata kunci: solusi masalah; kondisi psikologis; kecemasan berbicara